African international doctoral students in New Zealand: Englishes, doctoral writing and intercultural supervision. Issue 1 (2nd January 2018) - Doyle, Stephanie; Manathunga, Catherine; Prinsen, Gerard; Tallon, Rachel; Cornforth, Sue
ABSTRACT: While the experiences of international doctoral students, especially those from Asian countries, have been well researched, fewer studies have explored the experiences of African students in Southern countries like Australia and Aotearoa/New Zealand. This article reports on doctoral writing and student and supervisor perspectives on English languages in a small study of supervisors and African students in New Zealand. It challenges deficit constructions of African students and illustrates how the growing internationalisation of higher education is adding to the complexities of doctoral writing, raising questions as to how students and supervisors recognise and navigate differences in Englishes and doctoral writing. It makes a number of recommendations about how supervisors might work effectively with African and other doctoral students.